God's good man; a simple love-story - Corelli, Marie; Dodd, Mead & Company (Dodd, Mead & company, 1904)
A novel of romantic and religious aspect in which a young clergyman falls in love with an attractive wealthy woman moving in smart Edwardian society.
A novel of romantic and religious aspect in which a young clergyman falls in love with an attractive wealthy woman moving in smart Edwardian society.
Keywords: Bookbinding / Specimens; Clergy / England / Fiction.; Romance fiction, English; England / Social life and customs / Fiction; Love stories / gsafd